Chinese Science Fiction in the Anthropocene. - Imbach, Jessica (Ecozon@, 2021)
A green future has become a central promise of the Chinese state and the environment is playing  an increasingly important role in China’s bid to promote itself as a political alternative to the West. However,  Chinese state environmentalism and its promotion of “ecological civilization” (shengtai wenming  ? ??? )  have so far proven more aligned with political interests rather than environmental goals. At the same time,  low -orbit  industrialization  as  a  response  to  the  climate  change  or  the  resurgent  fantasy  of  p opulation  control  as  a  necessity  from  the  standpoint  of  biology  in  environmentalist  discourse  are  increasingly   entangled with anxieties and speculations about Chinese visions of the future. Using Liu Cixin’s short story  The Sun of China  ( Zhongguo  taiyang ??? , 2001) and the 2019 blockbuster science fiction movie  The  Wandering Earth  ( Liulang diqiu ??? ) by Frant Gwo as its point of departure, this paper discusses how  current narratives of the Anthropocene are reflected and negotiated in Chinese science fiction. While both works demonstrate the symbolic and economic importance of science and technology to China’s growth and  self-image, they also reveal that we cannot separate questions of the planetary from the historical contexts, in which they emerge.